The Milestones of Forensic Medicine in Turkey: Prof. Dr. Fahri Ecevit - Buran, Cudi Ferat; Özkara, Erdem (The Bulletin of Legal Medicine, 2017)
Prof. Dr. Fahri Ecevit, after graduating from the Darülfünun-i Şahane (Faculty of Medicine of Istanbul University) served as a medical doctor was in different regions of Anatolia during the Independence War period. He was a Republican intellectual who served as a lecturer in the Ankara Law School as a Forensic Medicine Expert during the foundation years of the Republic and also a member of the Turkish political history in 1943-1950 as a parliamentarian. In addition to taking part in the education of numerous law school students as a lecturer, he has signed many scientific works. He has also participated in Forensic Medicine interviews held in Ankara Community House and participated in radio programs and has been a columnist at Ulus Newspaper. In short, forensic science has emerged from academia and has undertaken an unusual but interesting role in integrating with the public. He has academically worked in fields such as; forensic tanatologia, forensic psychiatry, medical law and civil law. During the two terms he served as parliamentarian, he interested in civil rights, children’s rights and the criminal responsibility of children and the position of the reformatory while he made speeches from the parliamentary council and in the commissions he served. In addition, he has made efforts especially to improve the working conditions of forensic medicine doctors. His ideas about the working conditions of forensic medicine doctors at that time are, keeps a light for today. The only children who came to the world from his wife, painter Fatma Nazli Hanım; Mustafa Bülent Ecevit is the well known figure of the Republic of Turkey and the political history of the world, where he has been involved for almost half a century; including as a Prime Minister of Republic of Turkey.